Upcycling of polyurethane waste by mechanochemistry: synthesis of N-doped porous carbon materials for supercapacitor applications - Schneidermann, Christina; Otto, Pascal; Leistenschneider, Desirée; Grätz, Sven; Eßbach, Claudia; Borchardt, Lars (Beilstein Journal of Nanotechnology, 2019)
We developed an upcycling process of polyurethane obtaining porous nitrogen-doped carbon materials that were applied in supercapacitor electrodes. In detail, a mechanochemical solvent-free one-pot synthesis is used and combined with a thermal treatment. Polyurethane is an ideal precursor already containing nitrogen in its backbone, yielding nitrogen-doped porous carbon materials with N content values of 1–8 wt %, high specific surface area values of up to 2150 m2·g−1 (at a N content of 1.6 wt %) and large pore volume values of up to 0.9 cm3·g−1. The materials were tested as electrodes for supercapacitors in aqueous 1 M Li2SO4 electrolyte (100 F·g−1), organic 1 M TEA-BF4 (ACN, 83 F·g−1) and EMIM-BF4 (70 F·g−1).
Keywords: mechanochemistry; polyurethane; porous carbon; supercapacitor; waste

(untitled) - Jambeck, J. R.; Geyer, R.; Wilcox, C.; Siegler, T. R.; Perryman, M.; Andrady, A.; Narayan, R.; Law, K. L. (Science, 2015)

Ocean plastic, Greenpeace UK

(untitled) - Geyer, R.; Jambeck, J. R.; Law, K. L. (Sci. Adv., 2017)

Plastic Pollution

(untitled) - Ignatyev, I. A.; Thielemans, W.; Vander Beke, B. (ChemSusChem, 2014)

(untitled) - Achilias, D. S.; Roupakias, C.; Megalokonomos, P.; Lappas, A. A.; Antonakou, E. V. (J. Hazard. Mater., 2007)

(untitled) - Goto, M. (J. Supercrit. Fluids, 2009)

(untitled) - Paszun, D.; Spychaj, T. (Ind. Eng. Chem. Res., 1997)

(untitled) - Sadat-Shojai, M.; Bakhshandeh, G.-R. (Polym. Degrad. Stab., 2011)

Market data, PlasticsEurope

(untitled) - Yu, K.; Taynton, P.; Zhang, W.; Dunn, M. L.; Qi, H. J. (RSC Adv., 2014)

(untitled) - Behrendt, G.; Naber, B. W. (J. Univ. Chem. Technol. Metall., 2009)

Polyurethanes

Polyurethanes Applications

Polyurethane Production, Pricing and Market Demand

(untitled) - Yang, W.; Dong, Q.; Liu, S.; Xie, H.; Liu, L.; Li, J. (Procedia Environ. Sci., 2012)

(untitled) - Nikje, M. M. A.; Garmarudi, A. B.; Idris, A. B. (Des. Monomers Polym., 2011)

Treatment and Disposal of Polyurethane Wastes: Options for Recovery and Recycling - Zevenhoven, R. (Helsinki University of Technology, 2004)
http://users.abo.fi/rzevenho/tkk-eny-19.pdf (accessed June 19, 2019).

(untitled) - Hulicova-Jurcakova, D.; Seredych, M.; Lu, G. Q.; Bandosz, T. J. (Adv. Funct. Mater., 2009)

(untitled) - Gratuito, M. K. B.; Panyathanmaporn, T.; Chumnanklang, R.-A.; Sirinuntawittaya, N.; Dutta, A. (Bioresour. Technol., 2008)

(untitled) - Thomas, B. N.; George, S. C. (Trends Green Chem., 2015)

(untitled) - Wang, G.; Zhang, L.; Zhang, J. (Chem. Soc. Rev., 2012)

(untitled) - Frąckowiak, E. (Phys. Chem. Chem. Phys., 2007)

(untitled) - Rodríguez-reinoso, F. (Carbon, 1998)

Carbon Materials for Catalysis - Serp, P.; Figueiredo, J. L. (John Wiley & Sons, 2009)

(untitled) - Serp, P. (Appl. Catal., A, 2003)

(untitled) - Ismail, A.; David, L. (J. Membr. Sci., 2001)

(untitled) - Kockrick, E.; Schrage, C.; Borchardt, L.; Klein, N.; Rose, M.; Senkovska, I.; Kaskel, S. (Carbon, 2010)

(untitled) - Presser, V.; McDonough, J.; Yeon, S.-H.; Gogotsi, Y. (Energy Environ. Sci., 2011)

Materials for Sustainable Energy - Steele, B. C. H.; Heinzel, A. (Materials for fuel-cell technologies, 2010)

(untitled) - Shao, Y.; Sui, J.; Yin, G.; Gao, Y. (Appl. Catal., B, 2008)

(untitled) - Antolini, E. (Appl. Catal., B, 2009)

(untitled) - Guo, D.; Shibuya, R.; Akiba, C.; Saji, S.; Kondo, T.; Nakamura, J. (Science, 2016)

(untitled) - Bruce, P. G.; Freunberger, S. A.; Hardwick, L. J.; Tarascon, J.-M. (Nat. Mater., 2012)

(untitled) - Wang, D.-W.; Zeng, Q.; Zhou, G.; Yin, L.; Li, F.; Cheng, H.-M.; Gentle, I. R.; Lu, G. Q. M. (J. Mater. Chem. A, 2013)

(untitled) - Schneidermann, C.; Kensy, C.; Otto, P.; Oswald, S.; Giebeler, L.; Leistenschneider, D.; Grätz, S.; Dörfler, S.; Kaskel, S.; Borchardt, L. (ChemSusChem, 2019)

(untitled) - Song, J.; Gordin, M. L.; Xu, T.; Chen, S.; Yu, Z.; Sohn, H.; Lu, J.; Ren, Y.; Duan, Y.; Wang, D. (Angew. Chem., 2015)

(untitled) - Zhang, L. L.; Zhao, X. S. (Chem. Soc. Rev., 2009)

(untitled) - Casco, M. E.; Kirchhoff, S.; Leistenschneider, D.; Rauche, M.; Brunner, E.; Borchardt, L. (Nanoscale, 2019)

(untitled) - Lota, G.; Grzyb, B.; Machnikowska, H.; Machnikowski, J.; Frackowiak, E. (Chem. Phys. Lett., 2005)

(untitled) - Krüner, B.; Odenwald, C.; Quade, A.; Kickelbick, G.; Presser, V. (Batteries Supercaps, 2018)

(untitled) - Borenstein, A.; Hanna, O.; Attias, R.; Luski, S.; Brousse, T.; Aurbach, D. (J. Mater. Chem. A, 2017)

(untitled) - Zhai, Y.; Dou, Y.; Zhao, D.; Fulvio, P. F.; Mayes, R. T.; Dai, S. (Adv. Mater. (Weinheim, Ger.), 2011)

(untitled) - Ewert, J.-K.; Weingarth, D.; Denner, C.; Friedrich, M.; Zeiger, M.; Schreiber, A.; Jäckel, N.; Presser, V.; Kempe, R. (J. Mater. Chem. A, 2015)

(untitled) - Wood, K. N.; O'Hayre, R.; Pylypenko, S. (Energy Environ. Sci., 2014)

(untitled) - Seredych, M.; Hulicova-Jurcakova, D.; Lu, G. Q.; Bandosz, T. J. (Carbon, 2008)

(untitled) - Mangun, C. L.; Benak, K. R.; Economy, J.; Foster, K. L. (Carbon, 2001)

(untitled) - Przepiórski, J.; Skrodzewicz, M.; Morawski, A. W. (Appl. Surf. Sci., 2004)

(untitled) - Xue, C.; Tu, B.; Zhao, D. (Adv. Funct. Mater., 2008)

(untitled) - Poliakoff, M. (Science, 2002)

(untitled) - Anastas, P.; Eghbali, N. (Chem. Soc. Rev., 2010)

(untitled) - Sheldon, R. A. (Green Chem., 2014)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Weyna, D. R.; Shattock, T.; Vishweshwar, P.; Zaworotko, M. J. (Cryst. Growth Des., 2009)

(untitled) - Delori, A.; Friščić, T.; Jones, W. (CrystEngComm, 2012)

Organic Mechanochemistry and Its Practical Applications - Todres, Z. V. (CRC/Taylor & Francis, 2006)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Klimakow, M.; Klobes, P.; Thünemann, A. F.; Rademann, K.; Emmerling, F. (Chem. Mater., 2010)

(untitled) - Friščić, T. (Chem. Soc. Rev., 2012)

(untitled) - Katsenis, A. D.; Puškarić, A.; Štrukil, V.; Mottillo, C.; Julien, P. A.; Užarević, K.; Pham, M.-H.; Do, T.-O.; Kimber, S. A. J.; Lazić, P.; Magdysyuk, O.; Dinnebier, R. E.; et al. (Nat. Commun., 2015)

(untitled) - Troschke, E.; Grätz, S.; Lübken, T.; Borchardt, L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Do, J.-L.; Friščić, T. (Synlett, 2017)

(untitled) - Schneidermann, C.; Jäckel, N.; Oswald, S.; Giebeler, L.; Presser, V.; Borchardt, L. (ChemSusChem, 2017)

(untitled) - Leistenschneider, D.; Jäckel, N.; Hippauf, F.; Presser, V.; Borchardt, L. (Beilstein J. Org. Chem., 2017)

(untitled) - Mio, H.; Kano, J.; Saito, F. (Chem. Eng. Sci., 2004)

(untitled) - Stolle, A.; Schmidt, R.; Jacob, K. (Faraday Discuss., 2014)

Handbuch Chemische Reaktoren - Borchardt, L.; Grätz, S. (Reaktoren für spezielle technisch-chemische Prozesse: Tribochemische Reaktoren, 2018)

(untitled) - Thommes, M.; Kaneko, K.; Neimark, A. V.; Olivier, J. P.; Rodriguez-Reinoso, F.; Rouquerol, J.; Sing, K. S. W. (Pure Appl. Chem., 2015)

(untitled) - McKee, D. W. (Fuel, 1983)

(untitled) - Thommes, M.; Morell, J.; Cychosz, K. A.; Fröba, M. (Langmuir, 2013)

(untitled) - Zhong, C.; Deng, Y.; Hu, W.; Qiao, J.; Zhang, L.; Zhang, J. (Chem. Soc. Rev., 2015)

(untitled) - Yan, R.; Antonietti, M.; Oschatz, M. (Adv. Energy Mater., 2018)

(untitled) - Borchardt, L.; Leistenschneider, D.; Haase, J.; Dvoyashkin, M. (Adv. Energy Mater., 2018)

(untitled) - Weingarth, D.; Zeiger, M.; Jäckel, N.; Aslan, M.; Feng, G.; Presser, V. (Adv. Energy Mater., 2014)